Analysis of Product Differentiation and Product Innovation on the Decision to Take Credit Through Competitive Advantage at Pt. Wahana Ottomitra Multiartha (WOM Finance) Sidoarjo Branch - Achmad Reza Mufthi; Yuniningsih Yuniningsih; Sugeng Purwanto (PT FORMOSA CENDEKIA GLOBAL, 2024)
The objectives of this research are to determine (1) the effect of product differentiation on the decision to take credit, (2) the effect of product innovation on the decision to take credit, (3) the effect of product differentiation on the decision to take credit through competitive advantage, and (4) the effect of product innovation on the decision to take credit through competitive advantage. The population in this study comprises 2,703 customers at PT. WOM Finance Sidoarjo Branch who have been regular customers for more than two years. The sampling technique used is purposive sampling, and the analysis method used is Partial Least Square (PLS). The results of this study indicate that (1) product differentiation can directly contribute to the decision to take credit, (2) product innovation can directly contribute to the decision to take credit, (3) product differentiation can contribute to the decision to take credit through competitive advantage, and (4) product innovation can contribute to the decision to take credit through competitive advantage.